2016
DOI: 10.4084/mjhid.2016.036
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance and Control of Antibiotic Resistance in the Mediterranean Region

Abstract: Antibiotic resistance is one of the most relevant problems in the healthcare: the growth of resistant microorganisms in healthcare settings is a worrisome threat, raising length to stay (LOS), morbidity and mortality in those patients.The importance of the antibiotic resistance and its spread around the world, gave rise to the activation of several surveillance systems, based especially on the collection of laboratory data to local or national level.The objective of this work is to carry out a review of the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…However, the rising prevalence of antimicrobial resistance in uropathogens, even in strains causing community-acquired uncomplicated infections, mainly for extended spectrum beta-lactamase (ESBL) production, and the increasing prevalence of invasive pan-resistant E. coli strains (resistant to aminoglycosides, fluoroquinolones and third-generation cephalosporins) suggest that a conservative approach to the use of these agents in community infections is warranted. 47,48 Nitrofurantoin Nitrofurantoin, a synthetic nitrofuran derivative, has been available for the treatment of UTIs since 1952. It still has relatively high activity against E. coli and E. faecalis uropathogens.…”
Section: Co-trimoxazolementioning
confidence: 99%
“…However, the rising prevalence of antimicrobial resistance in uropathogens, even in strains causing community-acquired uncomplicated infections, mainly for extended spectrum beta-lactamase (ESBL) production, and the increasing prevalence of invasive pan-resistant E. coli strains (resistant to aminoglycosides, fluoroquinolones and third-generation cephalosporins) suggest that a conservative approach to the use of these agents in community infections is warranted. 47,48 Nitrofurantoin Nitrofurantoin, a synthetic nitrofuran derivative, has been available for the treatment of UTIs since 1952. It still has relatively high activity against E. coli and E. faecalis uropathogens.…”
Section: Co-trimoxazolementioning
confidence: 99%
“…Therefore, knowledge of the general and local epidemiology and resistance profiles is of paramount importance in the optimal treatment of febrile neutropenia. 65,66 The most frequent bacteria causing infections in acute leukemia patients are summarized in Table 1. [67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] Previous studies have documented bloodstream infections in 15-38% of patients with hematological malignancies.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…90 In several European countries,> 10% of invasive infections caused by E. coli were due to extended-spectrum betalactamases (ESBL). 66,91 Pseudomonas aeruginosa (P. aeruginosa) is a Gram-negative pathogen associated with high mortality, and accounts for approximately 5-10% of BSI in hematological patients. 92 P aeruginosa is characterized by several resistance mechanisms; (i) intrinsically resistant to antimicrobial agents due to low permeability of its cell wall, (ii) genetic capacity to express a vast repertoire of resistance mechanisms, (iii) become resistant through mutations in regulative resistance genes, and (iv) acquire additional resistance genes from other organisms via plasmids, transposons and bacteriophages.…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…Nevertheless, it seems that if fundamental principles such as short duration of symptoms and anti-biofilm antibiotic therapy are upheld, success of DAIR procedure can be just as good in this group of patients 35 - 38 . The key problem in managing Gram negative PJI is the growing antibiotic resistance pattern, especially in the Middle East and Asia as well as in the European Mediterranean region 39 , 40 . It has been shown that the prognosis after DAIR is dramatically decreased when fluoroquinolone resistance is found 36 .…”
Section: Indications and Risk Factors For Failurementioning
confidence: 99%
“…It has been shown that the prognosis after DAIR is dramatically decreased when fluoroquinolone resistance is found 36 . Furthermore, even more serious problems such as combined resistance to third-generation cephalosporins, fluoroquinolones and aminoglycosides are often encountered, greatly reducing antibiotic treatment alternatives 39 . Carbapenemase-producing Enterobacteriaceae are also on the horizon and have already been implicated in PJI with dire consequences 41 .…”
Section: Indications and Risk Factors For Failurementioning
confidence: 99%